Crisis or Contentment? A Mixed-Method Exploration of Psychosocial Factors Influencing Meaning in Life During Midlife - Aditi Bhatia; Diksha Laungani; Lynda Hyland; Anita Shrivastava Kashi (SAGE Open)
The concept of meaning in life has received growing empirical interest over the last decade; however, it remains less explored in the context of midlife transition. This mixed-method study assesses factors associated with the search for and presence of meaning in life in a sample of middle-aged adults residing in the United Arab Emirates. Multiple regression analysis of data from 152 participants revealed that personal growth and self-compassion, but not materialism, significantly predicted the search for and presence of meaning in life. Qualitative data from five participants were analyzed using Interpretative Phenomenological Analysis (IPA). Three central themes were identified- “lessons learnt from the midlife transition,”“spirituality redefined at midlife,” and “growing through giving.” The findings contribute to the domains of humanistic psychology and counselling practice. Researchers recommend shifting from the crisis approach to a more positive, growth-oriented view of midlife.